Influence of carbon and phosphorus doping on electronic properties of ZnO - Sharma, Vidhika; Prasad, Mohit; Jadkar, Sandesh; Pal, Sourav (Journal of Materials Science-Materials in Electronics, 2016)
ZnO is one of the most promising candidate for photoelectrochemical splitting of water for hydrogen production. To increase the efficiency of ZnO based photoelectrochemical cell, its band-gap and band edges should be tailored to match visible light spectra and water redox potential respectively. In this paper, First-principles density functional theory calculations have been performed to evaluate the effect of non-metal dopants on electronic properties of ZnO. The model structures of X-doped ZnO were constructed using 32-atom 2 x 2 x 2 supercell of wurtzite ZnO with one O atom replaced with X (carbon C, phosphorus P). With respect to the electronic band structure, C (2p), P (3p) states are located above the valence band maximum of ZnO and mixing of these states is feeble to produce significant band gap narrowing. Doping of these non-metals dopants helps in the creation of isolated states which enhances visible light absorption of ZnO. Our theoretical calculations are consistent with the experimental results of C (P) doped ZnO and fully explains its visible light activity on non-metal doping.